Why Eco‐labels can be Effective Marketing Tools: Evidence from a Study on Italian Consumers. (4th December 2013) - Testa, F.; Iraldo, F.; Vaccari, A; Ferrari, E.
ABSTRACT An emerging topic in environmental management studies is the role of eco‐labels in guiding consumers in their purchasing choices. In order to contribute to the current debate on this topic, this research paper aims to assess, through a quantitative analysis, whether the knowledge, awareness and information that consumers gather on the environmental impact of a product through an eco‐label can stimulate an eco‐friendly behavior. Moreover, we assess whether general attitudes in purchasing behaviors determine a personal attitude toward ecological consumption. The findings from this study, which is based on a large dataset of Italian consumers, highlight a significant role of eco‐labels in increasing the consumer's perceived behavioral control, unlike loyalty in brand and in store, which do not exert a significant influence. Practical implications for green business strategies emerge. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment